Bootstrap of kernel smoothing in nonlinear time series - Franke, Jürgen; Kreiß, Jens-Peter; Mammen, Enno (Bernoulli, 2002)
Kernel smoothing in nonparametric autoregressive schemes offers a powerful tool in modelling time series. We show that the bootstrap can be used for estimating the distribution of kernel smoothers. This can be done by mimicking the stochastic nature of the whole process in the bootstrap resample or by generating a simple regression model. Consistency of these bootstrap procedures will be shown.
Gesehen am 05.02.2018